2015
DOI: 10.1016/j.amjcard.2015.02.050
|View full text |Cite
|
Sign up to set email alerts
|

State Mandated Public Reporting and Outcomes of Percutaneous Coronary Intervention in the United States

Abstract: Public reporting has been proposed as a strategy to improve health care quality. Percutaneous coronary interventions (PCIs) performed in the United States from July 1, 2009, to June 30, 2011, included in the CathPCI Registry were identified (n = 1,340,213). Patient characteristics and predicted and observed in-hospital mortality were compared between patients treated with PCI in states with mandated public reporting (Massachusetts, New York, Pennsylvania) and states without mandated public reporting. Most PCIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Advocates argue that public reporting enables patients to identify the best physicians and hospitals, simultaneously giving clinicians and health care organizations incentives to improve quality (31). Some studies have shown associations between public reporting and higher quality of care (32,33). Opponents counter that data used in some measures lack adequate clinical granularity to accurately reflect quality or that outcomes reporting may encourage denial of care to the sickest patients who might benefit most from treatment, but are also at highest risk for poor outcomes (3441).…”
Section: Benefits and Concerns Related To Public Reportingmentioning
confidence: 99%
“…Advocates argue that public reporting enables patients to identify the best physicians and hospitals, simultaneously giving clinicians and health care organizations incentives to improve quality (31). Some studies have shown associations between public reporting and higher quality of care (32,33). Opponents counter that data used in some measures lack adequate clinical granularity to accurately reflect quality or that outcomes reporting may encourage denial of care to the sickest patients who might benefit most from treatment, but are also at highest risk for poor outcomes (3441).…”
Section: Benefits and Concerns Related To Public Reportingmentioning
confidence: 99%
“…However, the better outcomes noted in this procedure-based analysis likely reflect some degree of case selection. 11 Collectively, the evidence to date suggests that public reporting impedes access to potentially life-saving interventions for the critically ill. 35,8,9 …”
Section: Current State Of Pci Public Reporting Initiativesmentioning
confidence: 99%
“…The latter finding was also observed in an analysis by Cavender et al of the CathPCI national registry – adjusted in-hospital mortality was lower among patients that underwent PCI for acute coronary syndrome in reporting compared with non-reporting states (OR 0.81; 95% CI 0.74–0.89). 6 …”
Section: The Impact Of Public Reporting On Outcomesmentioning
confidence: 99%
“…6 It is still unclear whether public reports actually improve care delivery before and after PCI, and if they motivate refinements in operator skillset, likely because the latter is difficult to measure. In the absence of this information, data on PCI outcomes in isolation is challenging to interpret as it is unclear to what extent variations in outcomes reflect true improvements in quality rather than provider risk aversion.…”
Section: The Impact Of Public Reporting On Outcomesmentioning
confidence: 99%